2021
DOI: 10.1103/physrevb.104.104104
|View full text |Cite
|
Sign up to set email alerts
|

Structural instability of transition metals upon ultrafast laser irradiation

Abstract: Precision in laser material structuring is critically defined by the energy flow during the irradiation process, particularly in ultrafast regimes. Alternative to thermal evolutions, nonequilibrium electronic excitation can exercise a direct influence on the atomic bonding delivering a potentially rapid destructuring process. In this context, the atomic disordering of transition metals (Cr, Ni and Ti) induced by non-equilibrium electronic excitation typical for ultrafast laser processing is studied with an emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…If the initial state is a solid, the lattice is heated due to electron–phonon energy transfer to a new thermal equilibrium over several (tens to hundreds of) picoseconds. During this evolution, many interesting effects such as the ultrafast electron and non-equilibrium phonon dynamics [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], changes in lattice stability [ 20 , 21 , 22 , 23 , 24 ], phase transitions [ 25 , 26 , 27 , 28 , 29 , 30 ], and non-equilibrium electron–phonon interactions [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] take place. It should be pointed out that these various physical processes are all driven by electronic excitations.…”
Section: Introductionmentioning
confidence: 99%
“…If the initial state is a solid, the lattice is heated due to electron–phonon energy transfer to a new thermal equilibrium over several (tens to hundreds of) picoseconds. During this evolution, many interesting effects such as the ultrafast electron and non-equilibrium phonon dynamics [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], changes in lattice stability [ 20 , 21 , 22 , 23 , 24 ], phase transitions [ 25 , 26 , 27 , 28 , 29 , 30 ], and non-equilibrium electron–phonon interactions [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] take place. It should be pointed out that these various physical processes are all driven by electronic excitations.…”
Section: Introductionmentioning
confidence: 99%
“…The metal target complex refractive index 55 is where optical properties at relatively high electronic temperatures (30,000 K) were used to emulate laser-material interaction and the excitation of the metal. This electronic temperature marks the beginning of material destructuring 67 and is regarded as a reasonable hypothesis for interaction with hot but not ablated walls.…”
Section: Experimental and Numerical Methodsmentioning
confidence: 90%
“…Lattice dynamics are of fundamental importance in a variety of fields, including phase transition [1], superconductivity [2], and thermal conductivity [3] It is reported that under intense laser radiation, the melting of the semiconductor will be athermal due to softening of interatomic bonds, which takes place long before the conventional thermal melting due to the process of energy transfer from electrons to ionic lattice [4]. For metals, however, the phenomenon of structural instability, phonon hardening, and phonon softening has been reported [4][5][6][7][8][9][10][11]. Recently, the lattice dynamics of Au-Cu alloys at warm dense state (WDM) have also been investigated [12].…”
Section: Introductionmentioning
confidence: 99%